All the way to America : the story of a big Italian family and a little shovel - Yaccarino, Dan (Alfred A. Knopf, 2011)
The story of four generations of an Italian American family, beginning with an immigrant who came through Ellis Island with big dreams, a small shovel, and his parents' good advice: "Work hard, but remember to enjoy life, and never forget your family."